Penerapan Sistem Penunjang Keputusan untuk Penyaluran Bantuan Sosial Berbasis Web Menggunakan Metode Simple Additive Weighting (SAW) (Studi Kasus : Kelurahan Pluit) - Muhamad Reza Ghifari; A. Nurul Anwar (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2026)
The distribution of social assistance is one of the government's efforts to improve community welfare and reduce poverty. Unfortunately, in current practice, the social assistance distribution process in Pluit Village is still carried out manually, resulting in various problems such as distribution delays, errors in data recording, and inaccurate recipient targeting. The system was developed using the Rapid Application Development (RAD) method, which emphasizes speed of development and active user involvement in every stage. This study aims to create a web-based Decision Support System (DSS) to help village officials determine social assistance recipients objectively. The Simple Additive Weighting (SAW) method is used to calculate the value of each candidate based on several criteria such as occupation, income, number of dependents, house condition, and building area. The results show that the system can help the selection process become faster and more objective. The results show that the developed decision support system is able to manage aid recipient data in a more structured manner, select recipients based on clear criteria, and produce aid recipient reports quickly and accurately.